Antilipase and antioxidant activity of Phyllanthus niruri ethanolic extract - Raja Abdul Rahman, Raja Noor Zaliha; Alias, Norsyuhada; Leow, Adam Thean Chor; Mohamad Ali, Mohd Shukuri; Ahmad Tajudin, Asilah; Salleh, Abu Bakar (American-Eurasian Network for Scientific Information, 2015)
The aim of this study is to determine the antilipase and antioxidant activity of Phyllanthus niruri methanolic extract. The inhibitory activity against porcine pancreatic lipase (PPL) was determined by measuring the hydrolysis of p-nitrophenyl butyrate to p-nitrophenol at 405 nm. The crude extract exhibited strong lipase inhibitory activity with an IC50 value of 27. 65 µg/ mL. The inhibition mode study disclosed that P. niruri could act as noncompetitive inhibitor. Antioxidant activity of P. niruri extract was measured by 2, 2, diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity assay. P. niruri showed high antioxidant activity with an EC50 value of 7.471 µg/mL. The results suggested that P. niruri has shown potential as a source of natural antilipase and antioxidant.